Company Directors (Malaysia & Singapore) : An Indepth Study Of Their Rights, Duties, Responsibilities, Rewards And Liabilities - Goh Chen Chuan
This is an in depth study of the rights, duties, responsibilities, rewards and liabilities of company directors.